A pilot project for the development of guidelines towards the establishment of a telecentre in a rural agricultural community in South Africa - Snyman, M.E. (Martha Elizabeth) (University of Pretoria, 2013)
Dissertation (MA (Development Communication))--University of Pretoria, 2006.